Depositional Sequences in Northern Peru: New Insights on the Palaeogeographic and Palaeotectonic Reconstruction of Western Gondwana During Late Permian and Triassic. Issue 6 (2021) - Carrillo, Emilio; Barragán, Roberto; Hurtado, Christian; Calderón, Ysabel; Martín, Germán; Vázquez-Taset, Yaniel; Parra, Mauricio; Rivera, Ariana; Cadena, Fanny Mariela; Sarmiento, Luis
No abstract available